Tailoring of Microstructures and Tensile Properties in the Solidification of Al-11Si(-xCu) Brazing Alloys - Bruno Monti Carmelo Donadoni; Leonardo Fernandes Gomes; Amauri Garcia; José Eduardo Spinelli (Metals, 2018)
Ternary Al-11wt %Si-(xwt %)Cu alloys are highly recommended as commercial filler metals for aluminum brazing alloys. However, very little is known about the functional inter-relations controlling the solidified microstructures characterizing processes such as torch and furnace brazing. As such, we evaluated two commercial brazing alloys, which are the Al-11wt %Si-3.0wt %Cu and Al-11wt %Si-4.5wt %Cu alloys: Cu contents typically trend in between the suitable alloying spectrum. We analyzed the effects of solidification kinetics over features such as the dendrite arm spacing and the spacing between particles constituting the eutectic mixture. Also, tensile properties were determined as a function of the dendrite microstructure dimensions. The parameters concerned for translating the solidification kinetics were either the cooling rate, or growth velocity related to the displacement of the dendrite tip, or the eutectic front. The relevant scaling laws representing the growth of these brazing alloys are outlined. The experimental results demonstrated that a 50% increase in Cu alloying (from 3.0 to 4.5 wt %) could be operated in order to obtain significant variations in the dendritic length-scale of the microstructure across the produced parts. Overall, the microstructures were constituted by an α-Al dendritic matrix surrounded by a ternary eutectic consisting of α-Al + Al2Cu + Si. The scale measurements committed to the Al2Cu eutectic phase pointed out that the increase in Cu alloying has a critical role on refining the ternary eutectic.